The hornet's nest : a novel of the Revolutionary War - Carter, Jimmy, 1924- (New York : Simon & Schuster, 2003)
A civil war story about Ethan Pratt, who finds himself influenced by competing forces.
Keywords: Southern States -- History -- Revolution, 1775-1783 -- Fiction; United States -- History -- Revolution, 1775-1783 -- Fiction; Historical fiction; War stories